Awareness and perception of adolescent boys about menstruation: an exploratory study from rural India - Daniel M. Abraham; F. B. Saliha (Discover Public Health)
Abstract Background/objectives Menstruation, despite being a natural process, remains stigmatized in many patriarchal societies, where taboos and misinformation perpetuate silence and misconceptions. This study investigates adolescent boys’ awareness and perceptions of menstruation in rural India, examining the influence of cultural, educational, and social factors on their understanding. Methods Employing an exploratory qualitative design, a focus group discussion (FGD) was conducted with eight 15-year-old boys from a rural secondary school in Kerala, India. The session was audio-recorded and supplemented with detailed field notes to capture verbal and non-verbal insights. Braun and Clarke’s thematic analysis framework was used to identify key themes. Results Three primary themes emerged: Levels of awareness (ranging from “correct but insufficient” to “lack”), Sources of knowledge (media, peers, cultural practices), and Desire for further knowledge. Findings indicate that fragmented or inaccurate knowledge, shaped by cultural and societal norms, reinforces stereotypes and stigma around menstruation. Conclusions Findings underscore the need for inclusive and culturally sensitive educational interventions for boys, aimed at dispelling myths and fostering empathy. Such programs can contribute to improved awareness, reduced stigma, and greater support for menstrual hygiene management (MHM) practices. Future research should assess similar interventions across broader contexts to determine their impact on challenging menstrual taboos.